PENDIDIKAN KEWARGANEGARAAN SEBAGAI SARANA PEMAHAMAN SISTEM PEMERINTAHAN INDONESIA - Mubarok, Aldi; Suherman, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Background: Theoretical understanding of state structures potentially triggers political apathy among the younger generation in the digital era. Objective: This study analyzes the strategic role of Civic Education (PKn) in enhancing students' understanding of the Indonesian government system. Research Methods: The method used is library research, exploring academic literature and policy documents from the past five years. Results and Discussion: The study shows that an adaptive Civic Education curriculum transforms constitutional theory into relevant practical understanding. Civic Education effectively internalizes the principles of checks and balances, enabling students to identify the authorities of executive, legislative, and judicial institutions, while increasing public participation in bureaucratic oversight. Conclusion: Teaching the government system through Civic Education is a preventive measure to maintain the stability of legal sovereignty and the integrity of Pancasila democracy, aiming to foster a younger generation that supports transparent governance.